Enzymatic Hydrolysis Systems Enhance the Efficiency and Biological Properties of Hydrolysates from Frozen Fish Processing Co-Products - Maria Sapatinha; Carolina Camacho; Antónia Juliana Pais-Costa; Ana Luísa Fernando; António Marques; Carla Pires (Marine Drugs)
Co-products from the frozen fish processing industry often lead to financial losses. Therefore, it is essential to transform these co-products into profitable goods. This study explores the production of fish protein hydrolysates (FPH) from three co-products: the heads and bones of black scabbardfish (Aphanopus carbo), the carcasses of gilthead seabream (Sparus aurata), and the trimmings of Nile perch (Lates niloticus). Four enzymatic hydrolysis systems were tested: an endopeptidase (Alcalase, A), an exopeptidase (Protana, P), two-stage hydrolysis with an endopeptidase followed by an exopeptidase (A + P), and a single stage with endo- and exopeptidase (AP). The results show that combined enzymatic treatments, especially single-stage Alcalase and Protana (AP), achieved high protein yields (80%) and enhanced degrees of hydrolysis (34 to 49%), producing peptides with lower molecular weights. FPH exhibited significant antioxidant activity, in 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays, with EC50 values below 5 mg/mL. Additionally, AP hydrolysates demonstrated over 60% angiotensin-converting enzyme (ACE) inhibition at 5 mg/mL, indicating potential antihypertensive applications. Antidiabetic and anti-Alzheimer activities were present, but at relatively low levels. AP hydrolysates, especially from gilthead seabream, proved to be the most promising. This study highlights the value of fish co-products as sources of functional peptides, contributing to waste reduction, and their potential applications in food, agriculture, and nutraceuticals.